Nano lithium silicates as flame-retardant impregnants for Pinus radiata - Canosa, Guadalupe (2011)
Aqueous solutions of nano lithium silicates with 5.5/1.0 and 7.5/1.0 silica/alkali molar ratios were used to impregnate Pinus radiata. To obtain these impregnants, a solution of 3.5/1.0 SiO2/Li2O molar ratio was used; this ratio was increased with nanosilica solution. The impregnations were realized using Bethell process. The curing was made with dibutylamine phosphate, a divalent cation and both chemicals used sequentially. Panels were tested in oxygen index (OI) chamber and two-foot tunnel. The statistical interpretation indicates that the best economical and technical performance was reached with impregnant of the highest silica content and with zinc cation for curing.